Beta-blockade for the treatment of cardiac arrest due to ventricular fibrillation or pulseless ventricular tachycardia: A systematic review and meta-analysis. (1st January 2020) - Gottlieb, Michael; Dyer, Sean; Peksa, Gary D.
Abstract: Background: Refractory ventricular fibrillation (VF) or pulseless ventricular tachycardia (VT) refers to cases that do not respond to traditional Advanced Cardiac Life Support measures and are associated with significantly lower survival rates. Beta-blockade may improve outcomes by protecting against the deleterious effects associated with epinephrine's beta-receptor effect. Objective: This systematic review and meta-analysis aimed to evaluate whether beta-blockade compared with control improved outcomes among patients in cardiac arrest due to refractory VF/VT. Methods: PubMed, Scopus, CINAHL, LILACS, the Cochrane databases, Google Scholar, and bibliographies of selected articles were assessed on September 2nd, 2019 for all studies evaluating beta-blockade versus control groups in patients with cardiac arrest due to refractory VF/VT. PRISMA guidelines were followed. Data were dual extracted into a predefined worksheet and quality analysis was performed with the Cochrane Risk of Bias in Non-randomised Studies of Interventions tool. Data were summarized and a meta-analysis was performed assessing temporary and sustained return of spontaneous circulation (ROSC), survival-to-admission, survival-to-discharge, and survival with a favorable neurologic outcome. Results: Three studies (n = 115 patients) were selected for final inclusion. Beta-blockade was associated with an increased rate of temporary ROSC (OR 14.46; 95% CI 3.63–57.57), sustained ROSC (OR 5.76; 95% CI 1.79–18.52), survival-to-admission (OR 5.76; 95% CI 1.79–18.52), survival-to-discharge (OR 7.92; 95% CI 1.85–33.89), and survival with a favorable neurologic outcome (OR 4.42; 95% CI 1.05–18.56). Overall risk of bias ranged from moderate-to-severe, which was primarily influenced by selection of participants and potential confounding. This study was registered with PROSPERO (CRD42019126902). Conclusions: The data suggest that beta-blockade may be associated with improved outcomes ranging from ROSC to survival with a favorable neurologic outcome. Future randomized controlled trials are needed to further evaluate this intervention in refractory VF/VT.